Tax Review Aspek Perpajakan Bagi Foreigner Atas Income Tax Evasion Penyewaan Kepemilikan Properti Di Indonesia - Rika Septiani; Raihanita Raihanita; Rima Mila Wati; Tiara Vergita Mahanani; Diana Setiawati; Hary Abdul Hakim (Borobudur Law and Society Journal, 2022)
There are various number of foreigners owned a property business in Indonesia which is then rented out. But in reality, there are still many parties who violate the lease, namely by way of leasing transactions carried out at foreign banks. So that the tax issued can be lower than it should be. The purpose of this study is to determine how the tax provisions for foreigners on rental property ownership in Indonesia and how the crime of tax evasion. From the point of view of criminal law, this is a violation of tax evasion which is regulated in the KUP Law, articles 38-40. The method used in this research is normative juridical which examines the normative aspects of legislation, namely legal research conducted by examining primary legal materials and secondary legal materials. In the implementation of taxes, there are many obstacles in the form of violations and tax evasion. In taxation, foreign nationals are also subject to domestic and foreign taxes. In the event of tax evasion on house rent by a foreigner, it can be criminally processed as regulated in the KUP Law articles 38-40.